Visual Militarization During Crisis: The Lenin Moreno and Sebastián Piñera's Cases During the Protests of October 2019 - Verdes-Montenegro, Francisco J. (2021)
Faced with the renewed prominence acquired by the military factor in Latin America and in particular the role that castrenses have played in various crises that have shaken the region throughout 2019, from Venezuela to Bolivia, through Ecuador or Chile, this work delves into what is defined as a process of “remilitarization” in the region. Specifically, it delves into a new feature int the armed forces in Latin America: being used with a visual component in situations of political crisis or when the policy-makers power is questioned. Therefore, first, the work deeps on the theoretical-methodological discussions in International Relations to analyze this visual component. Subsequently, the dynamic of remilitarization that emerged in Latin America will be presented from a historical perspective, pointing out its main features as well as the effects in the region. And in the end, it will be completed with a visual and verbal discourse analysis of qualitative character that will pay attention to the role played by the Latin American armed forces in two political crises that have erupted during October 2019 in the region: Ecuador and Chile. Then, a double message is projected visually: on one hand, the support of the Armed Forces when the president’s leadership is questioned; and on the other side, the attempt to dissuade those who support protests.